Molecular Detection of Panton Valentine Leukocidin Toxin in Clinical Isolates of Staphylococcus aureus from Kiambu County, Kenya - Sani Iliya; Jonathan Mwangi; Ronald Maathai; Mary Muriuki; Christopher Wainaina (International Journal of Microbiology)
Panton–Valentine leukocidin gene is produced by Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus isolates as a pore-forming toxin is largely responsible for skin and soft tissue illnesses. MRSA produces PVL toxins through lukS and lukF proteins causing tissue necrosis by damaging membrane of the defense cells. Presence of PVL toxin was tested from the 54 S. aureus clinical isolates obtained from Thika and Kiambu Level 5 Hospitals, in Kiambu County, Kenya, by Geno Type® MRSA assay (Hain Life Science, Nehren, Germany). DNA was isolated from freshly harvested bacterial cultures by spin column using Geno Type DNA isolation kit. The detection of PVL toxins was performed by amplification of genomic DNA and by reverse hybridization that identifies PVL genes using Geno Type MRSA kit. Out of 138 samples that were collected from patients in Kiambu County, 54 S. aureus isolates were obtained, of which 14 (25.9%; 95% CI = 11.9–38.9) samples had PVL toxins. The isolates that were obtained from the female patients had a higher PVL toxin prevalence of 35.7%, while the isolates collected from the male patients had a lower prevalence of 15.4% (P=0.09). The pediatrics department had the highest PVL gene prevalence compared to outpatient department and surgical units (P=0.08). However, the age groups of patients and the hospital attended by patients showed no significant difference in terms of PVL gene prevalence (P=0.26). Therefore, the patients' gender and hospital units were not significantly associated with PVL gene prevalence (P=0.08). This study shows that PVL positive isolates occur in the sampled hospitals in the county and female as well as children must be taken into consideration among patients with wound infections when isolating S. aureus.